Assessing the influence of lived-experience experts on healthcare providers in a virtual community of practice: a qualitative study - Stephanie Sargent Weaver; Monique Carry; Jeanne Bertolli; Job Godino; Job Godino; Bruce Struminger; Douglas Taren; John D. Scott; Sydney P. Sharp; Jane Samaniego; Donna R. Bean; Anindita Issa; et al. (Frontiers in Health Services)
Long COVID, myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS), and other poorly understood post-acute infection syndromes (PAIS) can present with unexplained symptoms or conditions that may be misunderstood by healthcare providers, causing delays in diagnosis and care. To address these issues, the Centers for Disease Control and Prevention (CDC) funded the Long COVID and Fatiguing Illness Recovery Program (LC&FIRP), initiated as a pilot project to assess whether providing tele-mentoring and other online education for primary care providers could help them improve the quality of life and support the recovery of their patients with these conditions. The LC&FIRP multi-disciplinary team-based care approach is built on the Extension for Community Healthcare Outcomes (ECHO) learning model, which is an evidence-based virtual learning framework developed by the University of New Mexico and designed to disseminate and implement best practices, especially in under-resourced areas. A distinctive feature of LC&FIRP was the inclusion of lived-experience experts. To explore the influence of lived-experience experts on the care patients received, we collected the educational recommendations provided by the lived-experience experts during webinar sessions (January 2022—March 2024) and grouped these by themes. The major themes that emerged included validation of patients’ illness experience; attitudes and beliefs about Long COVID, ME/CFS, and PAIS; understanding patients’ challenges and communicating with empathy; navigating referrals; recognizing and supporting disability; and supporting self-care. Investigators also interviewed patients of the Family Health Centers of San Diego (FHCSD) about their experiences receiving care from participating primary care providers and employed content analysis methods to code interview transcripts to identify themes among patients’ perspectives. Positive comments from the patients about topics emphasized by the lived-experience experts provided evidence of providers’ uptake and application of the experts’ recommendations and support the value of involving lived-experience experts in medical education to improve health services.